Synergy between DUNE and T2HKK to probe invisible neutrino decay - Zannatun Firdowzy Dey; Debajyoti Dutta (Journal of High Energy Physics)
Abstract We address the consequence of invisible neutrino decay within the framework of two long base-line neutrino experiments: T2HKK (Tokai-to-Hyper-Kamiokande-to-Korea) and DUNE (Deep Underground Neutrino experiment). Our primary objective is to bring out the aspects of CC (charged current) and NC (neutral current) measurements at DUNE in the context of invisible neutrino decay. We find that the inclusion of NC measurements with the CC measurements enhances its ability to constrain invisible neutrino decay. Further, the synergy between DUNE and T2HKK improves the constraints on invisible neutrino decay. At 3σ C.L. (confidence level) the derived constraint is τ 3 /m 3 ≥ 6.21 × 10 −11 s/eV. Additionally, if nature prefers ν 3 to be unstable and the decay width is τ 3 /m 3 = 2.2 × 10 −11 s/eV, this combination can exclude the no-decay scenario at more than 5σ C.L. Although the CP sensitivity is not much hindered in the presence of invisible neutrino decay, the measurements of θ 23 and the ability to resolve octant of θ 23 is significantly influenced in these individual experiments. In the presence of invisible neutrino decay, the synergy between DUNE and T2HKK can exclude the wrong octant somewhat more effectively than either experiment alone.